SEG Technical Program Expanded Abstracts 2005 2005
DOI: 10.1190/1.2148263
|View full text |Cite
|
Sign up to set email alerts
|

3C VSP tomography inversion for subsurface P‐ and S‐wave velocity distribution

Abstract: First break times (FBT) of P-wave and S-waves picked from three-component (3C) VSP data were used to produce tomographic velocity profiles and Vp/Vs ratio distribution. 3C Eigenvalue rotation is critical for correctly identifying and accurately picking FBTs of S-waves. The resultant tomographic images provide important information for formation evaluation and produce suitable velocity models for improving migration imaging of subsurface structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Another common usage of first breaks in land seismic data is for geometry error corrections (Martin, 2001) and near-surface velocity model building using tomographic inversion of first arrival data (Colombo et al, 2016). In marine and ocean bottom node (OBN) data, first breaks have been used to estimate the depth of sources and hydrophones in deep-towed streamer acquisition (Walia & Hannay, 1999), in vertical seismic profile data processing for full velocity model building from P and S wave direct arrivals (Li et al, 2005) and to diagnose water velocity models and to detect spatial variations in the water velocity in the processing of OBN data (Li et al, 2015), which can be crucial for 4D processing.…”
Section: The Use Of First Breaks In Seismic Processingmentioning
confidence: 99%
“…Another common usage of first breaks in land seismic data is for geometry error corrections (Martin, 2001) and near-surface velocity model building using tomographic inversion of first arrival data (Colombo et al, 2016). In marine and ocean bottom node (OBN) data, first breaks have been used to estimate the depth of sources and hydrophones in deep-towed streamer acquisition (Walia & Hannay, 1999), in vertical seismic profile data processing for full velocity model building from P and S wave direct arrivals (Li et al, 2005) and to diagnose water velocity models and to detect spatial variations in the water velocity in the processing of OBN data (Li et al, 2015), which can be crucial for 4D processing.…”
Section: The Use Of First Breaks In Seismic Processingmentioning
confidence: 99%
“…He showed that when Poisson's ratio of the upper layer is larger than the lower layer, P-waves from the upper layer propagating downward to the interface at small angles can produce transmitted converted S-waves. Zhao et al (2005) considered that in some P-wave source zero-offset VSP records, the main reasons for the observed pure S-waves produced near the source are: the shear component of the seismic source, near-source heterogeneity, and seismic anisotropy near the source. Li et al (2005) used the observed VSP downgoing P-and S-waves in a P-and S-wave velocity inversion.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, an available 'best' surface seismic velocity model will be used as an initial velocity model for 3D VSP imaging and then the model is updated by VSP First Arrival Time (FAT) tomography and rarely by VSP reflection tomography. Unfortunately, VSP tomography practices (e.g., Li et al 2003aLi et al , 2005 indicated a typical RMS misfit of over 100 ms for the initial velocity models used for the walk-away VSP and/or 3D VSP with offsets and depths of up to 6 km, implying velocity models are questionable in poorly illuminated regions by surface seismic survey. Although VSP tomography can bring RMS misfits significantly down to about 10-20 ms, sometimes, resulting velocity models are neither unique nor make sense geologically, due to limited receiver coverage and the low fold coverage of VSP surveys.…”
Section: Introductionmentioning
confidence: 99%